THE IMPACT FROM RETURN OF EQUITY (ROE), RETURN OF ASSET (ROA), AND EARNING PER SHARES (EPS) ON PRIMARY CONSUMER SECTOR (CONSUMER NON-CYCLICALS) COMPANIES ON THE IDX DURING 2014-2019 - Risyafli, Izzan Qinthar; Chaerudin, Chaerudin (Dinasti Publisher, 2021)
This research has written with aim of classifying and analyzing the influence of Return on Assets (ROA), Return on Equity (ROE) and Earning Per Share (EPS) towards stock prices in consumer goods companies which registered on the IDX during period of 2014-2019. This research used a quantitative method with secondary data to be processed. The sampling technique that used in this research was purposive and saturated sampling technique and the samples obtained were INDF (Indofood), JPFA (Japfa), Sari Roti, Siantar Top and Sekar Laut. The research method used was multiple linear regression analysis method. The results in this research was indicate that 1) ROA has no significant impact on stock prices; 2) ROE has no impact on stock prices; 3) EPS has a significant impact on stock prices; 4) ROA, ROE and EPS simultaneously affects the stock prices.